A systematic review on the health aspects of the use ofexoskeletons at the workplace and development of asurvey on the attitude of employees - Anja Holz (2019)
Background: A majority of the European as well as the German workforce reported having been exposed to posture-related risks which play a major role in the development of musculoskeletal disorders and leads to a high number of days of incapacity to work and costs due to loss of production. Technology as forklifts, carts, hoists and industrial robots have shown to have a limited capacity to support the worker during different work tasks requiring flexibility and decision-making. With the rapid progress in technology, the use of occupational exoskeletons provides the opportunity to maintain the employees’ flexibility, creativity and decision-making power while at the same time gain a less strenous workplace by providing external support. The aim of this scientific study is to systematically search, qualitatively assess, evaluate and present literature on physical and psychological health aspects associated with the use of occupational exoskeletons. Furthermore, the results of the systematic review are used for the conceptual development of a survey investigating the attitude of employees towards the use of exoskeletons. Methods: A comprehensive literature search in ScienceDirect, PubMed, Cochrane Library, PsychInfo and Web of Science was conducted and the reference lists of relevant articles were screened. Information was gathered on potential physical and psychological health aspects associated with the use of occupational exoskeletons. Based on the results of the sytematic review a concept of a survey investigating the attitude of employees towards the use of exoskeletons at the workplace was developed. Results and Conclusion: 38 studies could be identified, the majority of them being experimental laboratory studies. Results showed that the use of occupational exoskeletons has overall positive effects on the wearer in the form of physiological and biomechnical parameters as well as positive effects on psychological aspects as wearing comfort, the employees’ attitude towards the use of occupational exoskeletons as well as the employees’ valuation of the exoskeleton’s effectiveness. Nevertheless, the results also showed the need for further research in this field as well as the need for the development of standardized tools to assess physical and psychological health aspects associated with the use of occupational exoskeletons. Based on the results of the previously conducted systematic review a conceptual survey in the form of a three-part questionnaire consisting of closed questions to measure the attitude of employees towards the use of exoskeletons at the workplace was developed. The three parts of the questionnaire allow for the meaurement of the employees’ attitude towards occupational exoskeletons at three different points in time. Therefore, a possible change in the employees’ attitude can be taken into accout. Keywords: Exoskeleton, Physical Health, Psychological Health, Occupation, Industry, Work, Questionnaire, Attitude